The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.0105-1873.2005.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental nickel elicitation thresholds – a review focusing on occluded nickel exposure

Abstract: Nickel (Ni) is the most frequent cause of contact allergy among the female population. This makes it interesting to examine thresholds for elicitation under different conditions. Even though Ni exposure may be open, occluded, penetrating or oral, most dose-response studies in the literature concern single occluded application. The aims of this study were to assess thresholds of response by making a statistical analysis of available dose-response studies with single occluded exposure and comparing the results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 39 publications
2
65
0
3
Order By: Relevance
“…Possible explanations could be the considerably smaller total amount of metal in the test compared with that in the real appliance, the relatively short exposure time, and the absence of mechanical irritation from smooth bands. [9][10][11] Regular smoking recently has been suggested to play a role in contact allergic reactions as well, although the mechanisms are not known. 12 When two metals come in contact, corrosion of the less precious metal is increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible explanations could be the considerably smaller total amount of metal in the test compared with that in the real appliance, the relatively short exposure time, and the absence of mechanical irritation from smooth bands. [9][10][11] Regular smoking recently has been suggested to play a role in contact allergic reactions as well, although the mechanisms are not known. 12 When two metals come in contact, corrosion of the less precious metal is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the immunology of the oral mucosa may differ from that of the skin, because the oral mucosa is potentially less reactive than the skin to contact allergens such as nickel. 10 According to current evidence, orthodontic treatment does not increase the risk of nickel allergy; neither has nickel allergy been shown to be an obstacle to treatment with fixed appliances made of stainless steel. 14,15 Yet, although most nickel-allergic patients can be treated without discomfort, individual variation exists, and orthodontic treatment occasionally may even aggravate the existing allergy, as may have happened in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A recent metaanalysis demonstrated that this limit is most likely reasonable. 35 Furthermore, the EU directive prohibits nickel in coated products, unless the coating is sufficient to ensure that the nickel release will not exceed 0.5 g/cm 2 /wk after 2 years of normal use. 12 Finally, it restricts the level of permitted nickel release in post assemblies (also called ''studs'' or simply ''posts'') at 0.2 g/cm 2 /wk.…”
Section: Discussionmentioning
confidence: 99%
“…Nickel itch or nickel allergy is a reaction that develops after repeated and prolonged exposure to nickel or nickel-containing items (12). For this reason, the European Union has set nickel release from items with prolonged skin contact at 0.2 µg per cm 2 (20).…”
mentioning
confidence: 99%